LAW ENFORCEMENT OF 2024 ELECTION OFFENCES IN CONSTITUTIONAL LAW PERSPECTIVE: A CASE STUDY - Aulia, Rahma (Journal Philosophy of Law, 2025)
Research discusses the challenges and problems faced in law enforcement related to offences of the 2024 simultaneous general elections in Indonesia with a focus on Central Java Province. Through a constitutional law approach, this study explores how Badan Pengawas Pemilu (Bawaslu) plays a role in enforcing the law and preventing offences. The method used in this research is normative juridical with empirical and statutory approaches. Data were collected through a qualitative method by analyzing cases of offences that occurred in Central Java. The results showed that in law enforcement against election offences, Bawaslu Central Java Province focuses on efforts to prevent election offences, with handling offences as the last step if prevention fails. Handling of election offences can come from two sources: namely supervision by election supervisors and reports from the public. If the offence is registered, Bawaslu conducts clarification and if proven, the criminal case is forwarded to the police and the Gakkumdu center, while code of ethics offences are submitted to DKPP and for administrative offences, Bawaslu holds an examination hearing that results in a binding decision. Bawaslu in handling election offences is faced with three challenges, namely multi-interpretive election rules, criminal allegations and a culture of people who are reluctant to report. Constitutional law plays a role in setting clear procedures, such as clarification by Bawaslu, investigation by Sentra Gakkumdu and examination hearings for administrative offences. In practice, justice and consistency in the application of sanctions are still needed, strengthening firmer regulations, increasing institutional capacity and legal protection for reporters.